9514 1404 393
Answer:
3) (x, y) = (-2, 8)
5) (x, y) = (-3, -7)
Explanation:
3) The expression for y can be substituted into the other equation.
4x +16 = 3x +14
x = -2 . . . . . . . . . . subtract 3x+16 from both sides
y = 3(-2) +14 = -6 +14 = 8
The solution is (x, y) = (-2, 8).
__
5) Substitute for y in the first equation.
-x +2(4x +5) = -11
-x +8x +10 = -11
7x = -21 . . . . . . . . . subtract 10
x = -3 . . . . . . . . . . . divide by 7
y = 4(-3) +5 = -12 +5 = -7
The solution is (x, y) = (-3, -7).